Place attachment among rural migrants and returnees: case of Shuangfeng County, China - He, Lei; Mao, Yingming; Kinoshita, Takeshi (Frontiers in Psychology, 2023)
In the mobile era, place attachment among rural migrants and returnees has become dynamic and diversified. However, research on place attachment to native place among rural migrants and returnees is limited. The focus of previous research has primarily been on the destination place attachment of rural migrants, which makes it difficult to gain a comprehensive understanding of the place attachment among both rural migrants and returnees. This study aims to investigate the state of place attachment to both native and destination places among rural migrants and returnees originating from the same birthplace. It explores their place attachment after migrating from rural areas to cities. A quantitative research approach was adopted, garnering questionnaire responses from 274 rural migrants and returnees, all born in Shuangfeng County, Hunan Province. The questionnaire encompassed a Likert scale for measuring place attachment, as well as sociodemographic statistical information. Exploratory factor analysis and confirmatory factor analysis were conducted to ascertain the reliability and validity of the questionnaire. Based on the factor scores of place attachment to both places from migrants and returnees, a two-step cluster analysis identified three types of migrants and two types of returnees. Chi-square tests revealed significant differences among migrants in terms of property ownership, educational level, marital status, presence of children, age at departure, and time away from hometown. The study discovered that, regardless of being a migrant or returnee, the overall attachment to hometown was stronger than that to the current or previously inhabited city. In the context of existing literature primarily concerned with the integration of rural migrants into urban areas, this paper offers a fresh research perspective, highlighting the significance of emotional ties to one's hometown for rural migrants. The findings of this paper provide direction and a theoretical basis for rural areas to attract return migration and for urban regions to facilitate the integration of migrants.